Single-cell bacterial transcription measurements reveal the importance of dimethylsulfoniopropionate (DMSP) hotspots in ocean sulfur cycling - Cherry Gao (Nature Portfolio, 2020)
DMSP is a ubiquitous organosulfur compound in the ocean that, once degraded by bacteria, plays key roles in global biogeochemical cycles and climate regulation. Here, the authors use single-cell measurements of transcription to investigate the intricate dynamics of bacterial DMSP degradation.